Understanding the engagement of elementary school students in one-to-one iPad programs using an adaptation of self-system model of motivational development - Tirado-Morueta, Ramón; Berlanga Fernández, Inmaculada; Vales-Villamarín, Helena; Guzmán-Franco, María-Dolores; Duarte-Hueros, Ana; Aguaded, Ignacio (Computers in Human Behaviour, 2020)
The number of one-to-one mobile programs in elementary schools as a resource that substitutes the textbook has become popular in worldwide. However, studies that seek to understand how the daily use of these mobile devices is associated with teaching/learning practices and student's engagement in the classroom are lacking. The authors utilized and adapted a self-system model of motivational development in order to better understand the mechanisms behind the promotion of academic engagement through the use of iPads. For this, an analysis using structural equations was conducted on the data collected from a network of 20 elementary schools and 1977 K-5/6 students in Spain, who used iPads daily in their Language, Mathematics, Science and Second Language subjects. The data showed that the pedagogic method acted as a mediator between iPad use in the classroom and academic engagement, as it satisfied the psychological needs of the students. The study contributes with a comprehensive approach that results in an increase of knowledge on the reasons behind the success of failure of these types of programs on learner engagement.
Keywords: collaborative learning; elementary education; mobile devices; authentic learning; engagement; one-to-one mobile programs; JCR; Scopus